Review on bioethanol as alternative fuel for spark ignition engines - Thangavelu, Saravana Kannan; Abu Saleh, Ahmed; Farid Nasir, Ani (Elsevier, 2016)
Bioethanol fuel obtained from biomass and bioenergy crops has been proclaimed as one of the feasible alternative to gasoline fuel, as it is considered to be clean, renewable and green. In this review, the bioethanol production techniques from different lignocellulosic biomass, and its potential ethanol yield are studied. Moreover, this paper has reviewed the effects of bioethanol fuel blends on spark ignition engine combustion characteristics (i.e. cylinder pressure, cylinder temperature, flame speed, combustion efficiency, combustion duration, heat release rate, knocking and cold start); engine performance parameters (i.e. torque, brake power, brake specific fuel consumption, brake mean effective pressure, brake thermal efficiency and volumetric efficiency); and emission characteristics (i.e. carbon monoxide, oxides of nitrogen, carbon dioxide, unburned hydrocarbon and other unregulated emissions).